METODE BERMAIN PERAN SEBAGAI UPAYA PENGEMBANGAN KETERAMPILAN SOSIAL ANAK USIA DINI: Studi Literature : - Sri Arum Reny Kusumawati (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
The purpose of this article is to describe use of role playing methods in developing early childhood social skills. This article uses a literature study method, data is collected through literature study from various references such as books and previous research result, then the data is analyzed descriptively. Early childhood is in the golden age where at that time all aspects of growth and development can grow and develop significantly, during the golden age it is necessary to provide appropriate stimulation acording to the phase of development, one of which is providing stimulation to the social-emotional aspect of early childhood. Social skills have a very big role in children’s lives because good social skills possessed by children will make it easier for children to interact with people around them. The results showed that role playing can develop early childhood social skills because in role playing there is interaction between individual with individual and individual with group where the interaction is part of social skills and these interaction activities can be used as a provision for children to socialize in the future.